Microstructure, mechanical and corrosion properties of extruded milled magnesium powder - Dvorsky, Drahomir; Kubasek, Jiri; Vojtech, Dalibor (Manufacturing Technology Journal, 2020)
Magnesium materials are interesting for application in medicine as biodegradable implants. There is an ef-fort to improve mechanical and corrosion properties for this application. Powder metallurgy seems to be a progressive method suitable for improving those demanded properties. Therefore, this paper deals with the preparation of pure Mg by extrusion of milled powder. The milling process should lead to better homogenei-ty of microstructure and the disturbing of the oxide layer on the powder particles. Also, the input deformation energy in the milled powder should affect the deformation and recrystallization process during extrusion. In this paper, the influence of extrusion temperature on microstructure, mechanical, and corrosion properties is evaluated. Higher extrusion temperature leads to the larger deformed grains in the extrusion direction and higher tensile strengths. On the other hand, the plasticity and compressive yield strengths are reduced with higher extrusion temperatures. Corrosion properties are negatively affected by the iron inclusions incorpo-rated in the structure during milling. Otherwise, corrosion resistance decrease with increasing extrusion tem-perature due to the grain size.
Keywords: Magnesium; extrusion; mechanical properties; corrosion; powder metallurgy.